Republic of Latvia : Selected Issues Paper. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2016)
The aim of this paper is to examine selected issues related to Latvia's economic development. Latvia experienced a large macroeconomic adjustment in the aftermath of the crisis in 2007. The adjustment was characterized by internal devaluation via a combination of wage restraint and productivity gains. Latvia's creditless recovery has taken unusually long to turn compared to international experience. Although lack of credit has not undermined recovery so far, support from the financial sector will be crucial for its continuation going forward. Emphasis on resuscitating credit growth is key to maintaining recovery. Focus should be on facilitating access to credit for small- and medium-sized enterprises and first-time borrowers, where market failures are the largest.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet